2021
DOI: 10.3390/ijerph18020505
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Impact of COVID-19 among Treatment-Seeking Smokers: A Mixed Methods Approach

Abstract: The consequences of the COVID-19 pandemic on behavioral health, including tobacco use, are not fully known. The current study sought to measure the perceived impact of COVID-19 and the resulting stay-at-home orders in Philadelphia, Pennsylvania and Buffalo, New York on smokers enrolled in four smoking cessation trials between March 2020 and July 2020. The survey collected quantitative data regarding life changes due to COVID-19, health/exposure status, and the impact on their cessation attempt (e.g., motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Perceptions of greater risks of both becoming infected and suffering severe complications were associated with an increased importance of quitting which suggests that smokers may be motivated to quit due to the threat of COVID-19. Smokers enrolled in smoking cessations trials during the pandemic reported that their motivation to quit was altered by the pandemic [35]. A study among smokers from the United Kingdom and Australia found that 45% of respondents wanted more information on smoking and COVID-19 health risks [36].…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of greater risks of both becoming infected and suffering severe complications were associated with an increased importance of quitting which suggests that smokers may be motivated to quit due to the threat of COVID-19. Smokers enrolled in smoking cessations trials during the pandemic reported that their motivation to quit was altered by the pandemic [35]. A study among smokers from the United Kingdom and Australia found that 45% of respondents wanted more information on smoking and COVID-19 health risks [36].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has also documented both increased and decreased smoking during the pandemic [9,10,12], with people reporting a variety of reasons for changes in their smoking, such as disrupted schedules and social situations [12,[14][15][16], financial and logistical constraints [12,15,16], and stress [12,[14][15][16]. While health concerns of smoking and COVID-19 contributed to decreased smoking [12,[14][15][16], other factors were also influential. Other studies using the HBM to predict behavior and behavioral intentions during the pandemic [21][22][23][24][25][26][27][28][29][30] have also produced mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stress from the pandemic was significantly associated with both increased smoking and decreased smoking. Prior research has also documented both increased and decreased smoking during the pandemic [ 9 , 10 , 12 ], with people reporting a variety of reasons for changes in their smoking, such as disrupted schedules and social situations [ 12 , 14 , 15 , 16 ], financial and logistical constraints [ 12 , 15 , 16 ], and stress [ 12 , 14 , 15 , 16 ]. While health concerns of smoking and COVID-19 contributed to decreased smoking [ 12 , 14 , 15 , 16 ], other factors were also influential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of American smokers were motivated to quit smoking during the pandemic. Some even found that pandemic-related restrictions like the 'stay-at-home' order made it easier to quit smoking due to less accessibility to cigarettes [66] . Kowitt et al reported that more than 70% of smokers in the United States (US) had intentions to quit tobacco and almost half of them attempted to quit in the first six months of the pandemic [67] .…”
Section: Tobacco Smoking Reduction and Cessationmentioning
confidence: 99%